Is the Rear Seat Belt Relevant in Urban India? - Sapna Tiwari; Sumanshi Singh; Raghuram Sekhar (Indian Journal of Vascular and Endovascular Surgery)
The mandated and prevalent use of front seat belts in 4 wheeler vehicles contrasts with the disregard for the rear seat belt usage. This case series of four instances of severe hyperextension injuries in rear seat unrestrained passengers having met with a low velocity head on collision, highlights the significant morbidity associated with the latter. While other injuries sustained by unrestrained passengers in the rear seat have been highlighted in literature, there is a paucity of data in regard to peripheral vascular injuries. Each case had a similar biomechanical presentation– that of hyperextended knee injury below the front seat of the car (as the unrestrained rear seat passenger slid below and ahead post collision) giving rise to traumatic popliteal artery thrombosis and rupture at the fixed P3 (Popliteal artery third segment) segment of the popliteal artery. Despite the timely presentation and avoidance of amputation, the similar history of unrestrained passengers the similar presentation of injury in each case led to the recognition of the major preventable factor: Rear seat belts restraint. The poor enforcement of the prevalent law in the country in this respect in alignment of laws all over the world, questions the disregard with respect to rear seat belt usage at an individual level. This article hopes to bring about the awareness of the potential public health impacts of such injuries and the possible prevention of the same.